2013
DOI: 10.1128/iai.00895-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NK Cell-Activating Receptor CRACC in Periodontitis

Abstract: Periodontitis is a highly prevalent, biofilm-mediated chronic inflammatory disease that results in the loss of the tooth-supporting tissues. It features two major clinical entities: chronic periodontitis, which is more common, and aggressive periodontitis, which usually has an early onset and a rapid progression. Natural killer (NK) cells are a distinct subgroup of lymphocytes that play a major role in the ability of the innate immune system to steer immune responses. NK cells are abundant in periodontitis les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Increased type 1 cytokine production by both dendritic cells and NK cells, following exposition to P. gingivalis, has been described, resulting in increased P. gingivalis -specific IgG2 [81] (Figure 4(C)). Aggregatibacter actinomycetemcomitans, a gram-negative anaerobic bacterium strongly associated with localized aggressive periodontitis [82], has been reported to indirectly induces CD2-like receptor activating cytotoxic cells (CRACC) on NK cells, via activation of dendritic cells and subsequent IL-12 signalling [83]. CRACC induction was reported to be more significantly pronounced in aggressive than chronic periodontitis and positively correlated with periodontal disease severity, subgingival levels of specific periodontal pathogens, and NK cell activation in vivo [83] (Figure 4(D)).…”
Section: Natural Killer Cells In Periodontitismentioning
confidence: 99%
“…Increased type 1 cytokine production by both dendritic cells and NK cells, following exposition to P. gingivalis, has been described, resulting in increased P. gingivalis -specific IgG2 [81] (Figure 4(C)). Aggregatibacter actinomycetemcomitans, a gram-negative anaerobic bacterium strongly associated with localized aggressive periodontitis [82], has been reported to indirectly induces CD2-like receptor activating cytotoxic cells (CRACC) on NK cells, via activation of dendritic cells and subsequent IL-12 signalling [83]. CRACC induction was reported to be more significantly pronounced in aggressive than chronic periodontitis and positively correlated with periodontal disease severity, subgingival levels of specific periodontal pathogens, and NK cell activation in vivo [83] (Figure 4(D)).…”
Section: Natural Killer Cells In Periodontitismentioning
confidence: 99%
“…In a recent study, Kramer et al. showed that the predominant natural killer cell activating molecule in periodontitis is CD2‐like receptor activating cytotoxic cells. The induction of CD2‐like receptor activating cytotoxic cells was significantly more pronounced in aggressive periodontitis than in chronic periodontitis and correlated positively with disease severity and natural killer cell activation.…”
Section: Natural Killer Cells In Periodontitismentioning
confidence: 99%
“…In other studies, circulating but not lymph node CD56+ NK cells are reduced in patients with acute coronary syndrome compared with patients with stable angina (Backteman et al, ). Given that NK cells are activated in periodontitis (Kramer et al, ; Wang et al, ) and periodontitis has been associated with cardiovascular disease (Tonetti, Van Dyke, and Working group 1 of the joint EFPAAPw, ), it is surprising that the role of NK cells in periodontitis‐accelerated atherosclerosis has not been investigated. Similarly, whether NK cells contribute to CMV aggravated atherosclerosis has not been investigated (Vliegen et al, ; Beziat et al, ).…”
Section: Introductionmentioning
confidence: 99%